Youth Access to School Salad Bars in the United States—2011 to 2014. Issue 1 (January 2018) - VanFrank, Brenna K.; Onufrak, Stephen; Harris, Diane M.
Purpose: To examine differences in students' access to school salad bars across sociodemographic groups and changes in availability over time. Design: Nonexperimental. Setting: Nationally representative 2011 and 2014 YouthStyles surveys. Participants: A total of 833 (2011) and 994 (2014) US youth aged 12 to 17 years. Measures: Youth-reported availability of school salad bars. Analysis: Multivariable logistic regression models were used to assess differences in school salad bar availability by sociodemographics and changes in availability from 2011 to 2014. Results: Youth-reported salad bar availability differed by age in 2011 and race/ethnicity in 2014, but not by sex, income, metropolitan residence, or region in either year. Salad bars were reported by 62% of youth in 2011 and 67% in 2014; the increase was not statistically significant ( P = .07). Significant increases from 2011 to 2014 were noted among youth aged 12 to 14 years (56%-69%; P < .01), youth of non-Hispanic other races (60%-85%; P < .01), and youth in the Midwest (58%-72%; P = .01). Conclusion: These results suggest that youth-reported access to school salad bars does not differ significantly across most sociodemographic groups. Although overall salad bar availability did not increase significantly from 2011 to 2014, some increases were observed among subgroups. Continued efforts to promote school salad bars through initiatives such as Let's Move Salad Bars to Schools could help increase access for the nearly one-third of US youth reporting no access.